‘Gotta keep the customer satisfied’: Puppeteers as director-surrogates in The Cabin in the Woods - Kooyman, Ben (Horror Studies, 2015)
Abstract The postmodern horror comedy The Cabin in the Woods by Goddard (2012) depicts the heavily engineered ritual sacrifice of a group of college students on a recreational getaway. The chief orchestrators of this sacrifice – dubbed ‘puppeteers’ by the film’s protagonists – are Sitterson and Hadley, who in the film clearly inhabit the role of horror director-surrogates. While the parallels between their work and the film-making process have been widely noted, little has been said about what their on-screen representation actually has to say about horror film-makers. This article identifies four key premises on which the narrative hinges – that Sitterson and Hadley are journeyman directors rather than auteurs, that the directorial process is collaborative rather than auteur-centred, that horror directors must work with a prescribed number of finite formulas, and that their work is of considerable societal value – elucidating within The Cabin in the Woods a dialectical dialogue around the role, value and function of contemporary horror film authorship.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ob3N0LjYuMS4xMDFfMQ